Pemanfaatan potensi lokal buah Nanas untuk meningkatkan perekonomian keluarga di Kecamatan Bangko Pusako Kabupaten Rokan Hilir - Meilda Wiguna; Hardi Hardi; Dasrol Dasrol; Sem Paulus Silalahi; Mudrika Alamsyah Hasan; Astrid Faradisty; Isma Mulyani (Unri Conference Series: Community Engagement, 2020)
Bangko Pusako is a sub-district in district Rokan Hilir, Riau. Mostly the native works as palm oil farm workers and pineapple farmer.Regardless, people need the knowledge to manage local potensial through understanding about business they’ll gonna run, the law, and also simple financial report to develop local potensial becoming potensial business.This program (communities devotion) has a goal to enhancing knowledge of society in Bangko Pusako, especially housewife and daughter of palm oil farm worker, about how pineapple fruit is processed as jam and dodol (traditional food of Indonesia) by diversification. Other goals include entrepreneurship foundation, business law, competitiveness analysis of processed pineapple products, and simply financial report’s training in term to manage business processed pineapple product diversification. So that it can improve the economic welfare of the family in the villages in the Bangko Pusako sub-district, Rokan Hilir district. From the results of the program evaluation, there have been several mothers who make pineapple jam and sell it to neighbors based on orders for cake jam and some sell lunkhead pineapple to schools which are packaged in small plastic.